DNAJC12-associated developmental delay, movement disorder, and mild hyperphenylalaninemia identified by whole-exome sequencing re-analysis. (December 2018) - Veenma, Danielle; Cordeiro, Dawn; Sondheimer, Neal; Mercimek-Andrews, Saadet
Abstract Hyperphenylalaninemia, movement disorder, and intellectual disability due to variants inDNAJC12 is a recently reported inherited neurotransmitter disorder. We report two new patients with this new genetic disorder. Patient 1 is a 6-year-11-month-old boy with mild hyperphenylalaninemia and global developmental delay (GDD). Seventeen-year-old male sibling of patient 1 had GDD from the first year of life. He had mild hyperphenylalaninemia at 11.5 years of age following his younger brother's diagnosis. He had low levels of homovanillic acid and 5-hydroxyindolacetic acid in the cerebrospinal fluid. Whole-exome sequencing (WES) was normal in 2016. After the first description ofDNAJC12 -associated hyperphenylalaninemia, dystonia, and intellectual disability in 2017, WES re-analysis identified a homozygous c.58_59delGG (p.(Gly20Metfs*2)) variant inDNAJC12 . His younger brother was homozygous for the same variant, confirming the diagnosis ofDNAJC12 -associated hyperphenylalaninemia, movement disorder, and intellectual disability. Mild hyperphenylalaninemia and GDD should warrant targetedDNAJC12 genetic testing for the early diagnosis ofDNAJC12- associated hyperphenylalaninemia, movement disorder, and intellectual disability.